An exploratory study based on a questionnaire concerning green and sustainable finance, corporate social responsibility, and performance: Evidence from the Romanian business environment - Cristina Raluca Popescu; Gheorghe N. Popescu (Journal of Risk and Financial Management, 2019)
Green and sustainable finance, corporate social responsibility and financial and non-financial performance are attracting widespread interest due to the challenging times that the business environment is currently facing. Moreover, green and sustainable finance, corporate social responsibility, and intellectual and human capital have become central issues in measuring organizations' success, competitive advantage and influence on the marketplace. This scientific paper seeks to address the relationship between corporate social responsibility, intellectual capital and performance, providing valuable insights and relevant evidence from a Romanian business environment. The questionnaire method was used for the targeted research objectives, which referred to: (a) Romanian organizations and local community understanding of green and sustainable finance, corporate social responsibility and intellectual capital; (b) corporate social responsibility actions taken by Romanian organizations and the local community; (c) main drivers of corporate social responsibility and intellectual capital in Romanian organizations; and (d) ways to enhance financial and non-financial performance of Romanian organizations with the aid of corporate social responsibility and intellectual capital. The findings support the idea of a strong relationship between corporate social responsibility, intellectual capital and performance in the Romanian business environment. Our work shows that, broadly speaking, Romanian entities operate on a socially responsible level, being aware of the importance and the advantages brought by both corporate social responsibility and intellectual capital when it comes to enhancing profit, productivity and performance. Our results are highly encouraging and may be validated by a larger sample size.
Keywords: 330; accounting; audit; biodiversity; business environment; causal factors; competitiveness; corporate governance; corporate social responsibility; correlation; economic and financial analysis; economic performance; empirical research; environmental protection; ethics and integrity; exploratory study; financial performance; green finance; innovation; intellectual capital; nonparametric indicators; performance indicators; questionnaire method; social performance; statistical association; sustainability; sustainable finance